2022
DOI: 10.1002/ehf2.14187
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum sodium level trajectories and survival in patients with heart failure

Abstract: Aims The effect of changes in serum sodium levels on the survival of patients with heart failure (HF) is unclear. We aimed to analyse the impact of serum sodium level trajectories on survival in intensive care unit (ICU) patients with HF. Methods A total of 4760 patients diagnosed with HF between 2001 and 2012 from the Medical Information Mart for Intensive Care III (MIMIC‐III) database were extracted. Of these patients, 1132 patients who died within 48 h of ICU admissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
1
0
1
Order By: Relevance
“…The association between reversal of hyponatraemia and improved survival has been reported previously 3,10,25 . In a recent study of 3628 AHF patients, with serum sodium concentrations measured every 6 h since admission, rapid changes in serum sodium (both rapid decline from hypernatraemia, and in contrast to in our study, rapid increase from hyponatraemia) were related to increased 1‐year mortality but in this case conceivably, the rapidity of change may have been a marker of underlying severity of sodium derangements 26 …”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The association between reversal of hyponatraemia and improved survival has been reported previously 3,10,25 . In a recent study of 3628 AHF patients, with serum sodium concentrations measured every 6 h since admission, rapid changes in serum sodium (both rapid decline from hypernatraemia, and in contrast to in our study, rapid increase from hyponatraemia) were related to increased 1‐year mortality but in this case conceivably, the rapidity of change may have been a marker of underlying severity of sodium derangements 26 …”
Section: Discussionsupporting
confidence: 66%
“…to in our study, rapid increase from hyponatraemia) were related to increased 1-year mortality but in this case conceivably, the rapidity of change may have been a marker of underlying severity of sodium derangements. 26 Notably, in our study, the association of hyponatraemia with long-term outcomes was observed only for mortality (all-cause, cardiovascular and HF), but not for first hospitalizations (all-cause, cardiovascular or HF). Lack of association between hyponatraemia and subsequent HF hospitalizations could be partially explained by more intensive diuretic treatment of hyponatraemic patients at hospital discharge compared to the reference group.…”
Section: Associations With Hyponatraemia At Admission and Sodium Chan...contrasting
confidence: 53%
“…First of all, due to their mode of action, diuretics remove water through sodium‐related mechanisms, which in the long run may lead to sodium depletion. Although it has never been demonstrated, at least part of the ominous signs of heart failure—hyponatremia and hypochloremia—may be related to chronic exposure to loop diuretics 2–4 . On the other hand, because sodium is needed for an adequate diuretic response (to loop diuretics), and at the same time, loop diuretics remove sodium from the body, a sort of vicious circle is created that hinders the diuretic response in the long run.…”
mentioning
confidence: 99%
“…Although it has never been demonstrated, at least part of the ominous signs of heart failure—hyponatremia and hypochloremia—may be related to chronic exposure to loop diuretics. 2 , 3 , 4 On the other hand, because sodium is needed for an adequate diuretic response (to loop diuretics), and at the same time, loop diuretics remove sodium from the body, a sort of vicious circle is created that hinders the diuretic response in the long run. In this mechanism (sodium depletion), diuretics probably indirectly activate the renin‐angiotensin‐aldosterone (RAA) system, which is meant to keep sodium homeostasis in our body.…”
mentioning
confidence: 99%